Analisis Pemerataan Pendidikan Tingkat Pendidikan Dasar Di Kabupaten Buru Provinsi Maluku - Suraya Mukadar; Budiono Budiono (Jurnal Kebijakan dan Pengembangan Pendidikan, 2019)
Abstract: Social justice can be realized by realizing equitable education. In a hierarchical distribution of education can be started from education at the regional and elementary level. This study aims to describe (1) the condition of even distribution of primary level education in Buru Regency, Maluku Province. (2) factors affecting the distribution of basic education in the Buru Regency in Maluku Province. (3) the efforts of the Buru Regency government in distributing basic education. This research was conducted with a descriptive qualitative approach. Sources of data and information from the head of the education office, the education office secretary, the school principal, and teachers. Data collection techniques in the form of document studies, observation activities, and interviews. Data analysis in this research is data reduction, data presentation, verification and conclusion drawing. The results showed that (1) lack of teaching staff and inadequate educational facilities; (2) the factors that influence the distribution of education in Buru Regency are: a) budget; b) lack of parental awareness of the importance of education; d) infrastructure; e) teaching staff; f) distance to reach one place to another. (3) the efforts that have been made by the Buru Regency government in making education equal are: a) budget management prioritizes important and urgent needs; b) socialization to the public about the importance of education; c) socialization to the public to participate in education free of charge and provide scholarships to disadvantaged communities; d) school renovation; e) equity of teachers.Keywords: Equality Factor, Education, Elementary School Abstrak: Keadilan sosial dapat direalisasikan dengan mewujudkan pendidikan yang merata. Secara hierarki pemerataan pada pendidikan dapat dimulai dari pendidikan di daerah dan tingkat dasar. Tujuan penelitian ini yaitu untuk mendeskripsikan (1) kondisi pemerataan pendidikan tingkat dasar di Kabupaten Buru Provinsi Maluku. (2) faktor yang mempengaruhi pemerataan pendidikan dasar di Kabupaten Buru Provinsi Maluku. (3) upaya pemerintah Kabupaten Buru dalam melakukan pemerataan pendidikan dasar. Penelitian ini dilakukan dengan pendekatan kualitatif deskriptif. Sumber data dan informasi dari kepala dinas pendidikan, sekertaris dinas pendidikan, kepala sekolah dan guru. Teknik pengumpulan data berupa studi dokumen, kegiatan observasi, dan wawancara. Analisis data dalam penelitian ini yaitu reduksi data, penyajian data, verivikasi dan penarikan kesimpulan. Hasil penelitian menunjukan bahwa: 1) kurangnya tenaga pengajar dan fasilitas pendidikan yang belum memadai; 2) faktor-faktor yang mempengaruhi pemerataan pendidikan di Kabupaten Buru adalah: a) anggaran; b) kurangnya kesadaran orang tua akan pentingnya pendidikan; d) sarana prasarana; e) tenaga pengajar; f) jarak untuk menjangkau tempat satu dengan tempat lainnya. 3) upaya yang telah dilakukan pemerintah Kabupaten Buru dalam melakukan pemerataan pendidikan adalah: a) pengelolaan anggaran memprioritaskan kebutuhan yang penting dan mendesak; b) sosialisasi kepada masyarakat tentang pentingnya pendidikan; c) sosialisasi kepada masyarakat agar berpartisipasi dalam pendidikan tanpa dipungut biaya dan memberikan beasiswa kepada masyarakat yang kurang mampu; d) renovasi sekolah; e) pemerataan guru.Kata kunci: Faktor Pemerataan, Pendidikan, Sekolah Dasar